'Lock to Live': development of a firearm storage decision aid to enhance lethal means counselling and prevent suicide. (13th October 2018) - Betz, Marian E; Knoepke, Christopher E; Siry, Bonnie; Clement, Ashley; Azrael, Deborah; Ernestus, Stephanie; Matlock, Daniel D
Abstract : Objectives: We sought to (1) clarify decision needs among suicidal adults with home firearm access; (2) identify accurate, unbiased and acceptable approaches for content and messaging; and (3) develop a tablet-delivered decision aid for firearm storage options. Methods: Following international standards, we used stakeholder interviews to develop a decision aid for the decision, 'what option(s) to choose to reduce home access to firearms for an adult at risk of suicide'. Participants were adults with personal or family history of suicidal ideation or behaviours, firearm ownership or employment in a firearm range or store, involvement in suicide prevention field, or work as emergency department or other healthcare provider. Results: Through 64 interviews, we created the 'Lock to Live' decision aid, which includes (1) introduction specifying the decision, (2) clarification of preferences and logistics, (3) table of storage options and (4) summary with specific next steps. The final tool had high user acceptability. Conclusions: Should the 'Lock to Live' decision aid prove useful in a pilot feasibility trial and subsequent testing, it could enhance lethal means counselling and help prevent firearm suicide.